KONSEP PENDIDIKAN AKIDAH DAN AKHLAK MENURUT GUSTI HAJI ABDUL MUIS - Muhammad Nur Effendi (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2021)
Abstract: Religious and moral education are parts or areas in Islamic education. It requires the support of all related aspects, at home, in school, in the community by parents, teachers, figures, scholars, educators are in the community. A righteous creed can give liberation from all taklid and submission to other than Allah. However, even as a being, reason can be relative, it is needed the guidance of revelation. That's where the role and function of religion are for humans. Religion is not only limited to teaching about good or bad norms (ethics). But religion further teaches about behaving, both to his Lord, to his neighbor, and to his environment with all his behavior, which is called moral morals. The purpose of moral education that Muis wants to achieve is to create or make the morals that mahmudah attached and become the nature and attitude in the life and life of muslims.